Answer:-
General solution of "y''+4y=0" is "y=A\\cos 2x+B\\sin 2x".
Let "y=A(x)\\cos 2x+B(x)\\sin 2x" and "A'(x)\\cos 2x+B'(x)\\sin2x=0". Then "y'=-2A(x)\\sin 2x+2B(x)\\cos 2x" and so "y''=-2A'(x)\\sin 2x+2B'(x)\\cos 2x-4A(x)\\cos 2x-4B(x)\\sin 2x".
We have "\\frac{1}{2\\sin 2x}=y''+4y=-2A'(x)\\sin 2x+2B'(x)\\cos 2x". Also we have "A'(x)\\cos 2x+B'(x)\\sin2x=0".
"-1=0\\cdot 2\\cos 2x-\\frac{1}{2\\sin 2x}\\sin 2x="
"=2(A'(x)\\cos 2x+B'(x)2\\sin2x)\\cos 2x-"
"-(-2A'(x)\\sin 2x+2B'(x)\\cos 2x)\\sin 2x=2A'(x)", so "A'(x)=-\\frac{1}{2}" and "A(x)=-\\frac{1}{2}x+A"
Since "0=A'(x)\\cos 2x+B'(x)\\sin2x=-\\frac{1}{2}\\cos 2x+B'(x)\\sin2x", we have "B'(x)=\\frac{1}{2}\\frac{\\cos 2x}{\\sin 2x}". Then "dB=\\frac{1}{2}\\frac{\\cos 2x}{\\sin 2x}=\\frac{1}{4}\\frac{d\\sin 2x}{\\sin 2x}=\\frac{1}{4}d\\ln|\\sin 2x|" and "B(x)=\\frac{1}{4}\\ln|\\sin 2x|+B"
We obtain "y=\\left(-\\frac{1}{2}x+A\\right)\\cos 2x+\\left(\\frac{1}{4}\\ln|\\sin 2x|+B\\right)\\sin 2x"
Answer: "y=\\left(-\\frac{1}{2}x+A\\right)\\cos 2x+\\left(\\frac{1}{4}\\ln|\\sin 2x|+B\\right)\\sin 2x"
Comments
Leave a comment